PERAN INTERAKSI SOSIAL TERHADAP POLA ASUH PERKEMBANGAN ANAK DI KELUARGA DALAM PANDANGAN ISLAM - Khoirun Nisa; Abdul Muhid (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
Family involvement in developing children's abilities and social behavior is very much needed through interaction as a medium of actualization. The role of parents and children will be the basis of influence on child development parenting. in social life a person needs to interact with other people and when interacting one finds the true nature of himself as a social creature who needs each other. The task of parents must continue to hone and educate their children so that they can always socialize and interact well This article aims to discuss how the role of social interaction on parenting child development in the family in Islamic view. because more or less parents ignore it busy with what is being done so there is no word of attention and indifference to children. And in essence, parents are the most important part as a benchmark for children's growth and development.